Analisis Keputusan Pembelian Konsumen Melalui E-Commerce Shopee di Kota Bandung - Widaningsih, Ulfa; Amalia, Sholihati (Ebiz Prima Nusa, 2022)
The development of technology today has a considerable influence on the community, one of the frequent influences in society today always wants everything instant to just go shopping, sometimes lazy to do. E-commerce is one of the examples of technological developments and is a place of online buying and selling transactions that are much in demand today. Shopee is one of the e-commerce that provides a place to bring together sellers and buyers to make transactions online and become one of the most visited e-commerce. This research was conducted to know the decision of consumer purchase through Shopee e-commerce in Bandung. Data is obtained by spreading the questionnaire through Google form. The research method used is a descriptive analysis method with a quantitative approach. The data analysis methods used are validity testing, reliability testing, and descriptive testing. Based on the results of the study, consumer purchasing decision through Shopee e-commerce consists of six dimensions: product selection, brand selection, distributor options, purchase time, purchase amount, and payment method which is consistently included in the strong category of determining purchase decisions with a value of 3.73. The highest dimensions are product selection dimensions and the lowest dimensions are payment method dimensions.